Impact of elevated pCO2 on the ecophysiology of Mytilus edulis - Thomsen, Jörn (2012)
Increasing atmospheric CO2 concentrations equilibrate with the surface water of the oceans and thereby increase seawater pCO2 and decrease [CO32-] and pH. This process of ocean acidification is expected to cause a drastic change of marine ecosystem composition and a decrease in calcification ability of various benthic invertebrates. The studied area, Kiel Fjord, is characterized by high pCO2 variability due to upwelling of O2 depleted and CO2 enriched bottom water. Within less than 50 years, eutrophication of the Baltic Sea has drastically increased the mean pCO2 in the fjord. The observed increase and also the rate of this acidification process is much higher than it is expected for the global ocean as a consequence of increasing atmospheric CO2 concentrations. In contrast to other areas subjected to elevated pCO2, calcifying invertebrates inhabit Kiel fjord and the benthic community is dominated by the blue mussel Mytilus edulis. Mussel larvae settle in the period of the year when highest pCO2 (800-2300 µatm) are encountered, which is, at the same time, the main growth period due to highest phytoplankton densities. In laboratory experiments, calcification rates of M. edulis are maintained at elevated pCO2 levels which are expected to occur by the year 2300. Only at high pCO2 above 3000 µatm, calcification is significantly reduced. One possible reason for this tolerance is the fact that even under control conditions, the extracellular body fluids (haemolymph and extrapallial fluid, EPF) of M. edulis are characterized by low pH and [CO32-] and high pCO2. Therefore, the EPF which is in direct contact with the shell is undersaturated with calcium carbonate also at current, low seawater pCO2. Under elevated pCO2, mussels do not buffer the extracellular acidosis by means of bicarbonate accumulation. Thus haemolymph pH and [CO32-] are reduced even further. Calcification might not be affected by the extracellular acidosis, as an amorphous calcium carbonate (ACC) precursor is most probably formed in intracellular ...